2015
DOI: 10.1016/j.appet.2015.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes to GM foods. The balancing of risks and gains

Abstract: In the paper we study the variables influencing attitudes to the use of two biotechnologies related to gene transfer within apples. Using Eurobarometer 73.1 survey data on biotechnology, science and technology, with 15,650 respondents, we study the extent these attitudes are determined by socio-economic and other variables. We found that attitudes to the risks and gains are determined by socio-economic variables and also by the individual's knowledge, scientific background, their parent's education in science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 43 publications
7
70
1
1
Order By: Relevance
“… Age: For age, we observe positive and negative relationships. On the one hand, studies demonstrated that older people were less willing to use or buy functional food (Brečić et al., ; Cranfield et al., ; Verneau, Caracciolo, Coppola, & Lombardi, ) or GM food (Canavari & Nayga, ; Hudson et al., ), were less accepting nanotechnology for food production (Kim & Kim, ), or were less willing to pay for GM food (Lusk et al., ). But, on the other hand, there are studies that show older people who were willing to pay more for innovative food (with respect to GM: Lusk & Rozan, ; non‐GM biofortification: Oparinde, Banerji, Birol, & Ilona, ; fortification: Kavoosi‐Kalashami et al., ; Siegrist et al., ; Vecchio et al., ), had less fear toward GM foods (González, Johnson, & Qaim, ; Laros & Steenkamp, ; Sjöberg, ; Titchener & Sapp, ), or had higher intention to buy functional food or nutraceutical products (Henson et al., ). Gender: Results of gender influences on food evaluation seem to be more consistent.…”
Section: Results Of the Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“… Age: For age, we observe positive and negative relationships. On the one hand, studies demonstrated that older people were less willing to use or buy functional food (Brečić et al., ; Cranfield et al., ; Verneau, Caracciolo, Coppola, & Lombardi, ) or GM food (Canavari & Nayga, ; Hudson et al., ), were less accepting nanotechnology for food production (Kim & Kim, ), or were less willing to pay for GM food (Lusk et al., ). But, on the other hand, there are studies that show older people who were willing to pay more for innovative food (with respect to GM: Lusk & Rozan, ; non‐GM biofortification: Oparinde, Banerji, Birol, & Ilona, ; fortification: Kavoosi‐Kalashami et al., ; Siegrist et al., ; Vecchio et al., ), had less fear toward GM foods (González, Johnson, & Qaim, ; Laros & Steenkamp, ; Sjöberg, ; Titchener & Sapp, ), or had higher intention to buy functional food or nutraceutical products (Henson et al., ). Gender: Results of gender influences on food evaluation seem to be more consistent.…”
Section: Results Of the Reviewmentioning
confidence: 99%
“…For Italian consumers, appearance 5 negatively affected the willingness to pay a premium price for functional snacks before tasting (nonsignificant after tasting) as consumer do not believe that these products are appealing (Pappalardo & Lusk, 2016). Naturalness 6 appeared to be an important and positive technology feature for consumers with regards to GM foods (Hudson, Caplanova, & Novak, 2015;Ronteltap et al, 2016). Technologies that were seen as more natural and newer were perceived less risky and more beneficial (Hudson et al, 2015).…”
Section: Frequency Of Factors In Chain Actors' Evaluation Behavior Stmentioning
confidence: 99%
See 3 more Smart Citations